Morphological Aspects of Acute Renal Injury in Cardiac Surgery - L. N. Zimina; G. A. Berdnikov; S. I. Rey; S. Yu. Kambarov (Неотложная медицинская помощь)
Summary. The use of endoscopic transsphenoidal access is an effective and safe method for the surgical treatment of pituitary adenomas (PA). In endoscopic transsphenoidal surgeries, there is a need to control intracranial pressure (ICP) for reposition and expansion of the tumor capsule. Currently, the main method for reducing ICP in transsphenoidal surgery is installation of an external lumbar drainage, which is associated with a number of complications.Aim of study. To improve the results of surgical treatment of patients with arterial hypertension using hypertonic saline solution.Material and methods. A clinical and anatomical analysis of material from 27 deceased patients who were treated in the cardiac surgery department of the Institute was carried out. Valve replacement was performed in 11 patients, aortic replacement - 2, valves and aorta - 7, combined operations - 7. The patient’s records, autopsy protocols, results of histological examination of surgical and autopsy material were studied. Already on the next day after surgery, an increase in serum creatinine by more than 25% was noted under the conditions of CBR. Morphological examination of the kidneys revealed acute pathological processes - necrosis of nephrocytes of the convoluted tubules in 59.3% of cases and dystrophic changes in 40.7% of cases against the background of chronic pathology (nephrosclerosis, vascular atherosclerosis, glomerulosclerosis, pyelonephritis, secondary contracted kidney). After coronary angiography with a radiopaque contrast agent (RCA), signs of excretory nephrosis were noted, often with fixation of the RCA in the loop of Henle, with tubulorexis and the formation of cell casts.